TCM underground : 50 must-see films from the world of classic cult and late-night cinema - De Chirico, Millie; Murry, Quatoyiah (Running Press, 2022)
Based on the Turner Classic Movies series, TCM Underground is the movie-lover's guide to 50 of the most campy, kitschy, shocking, and weirdly wonderful cult films you need to see. In the pages of this book, you'll explore this unique order of films--primarily from the 1960s, '70s, and '80s--with insightful reviews, behind-the-scenes stories, subgenre sidebars, and full-color and black-and-white photography throughout. Go along for the ride with new takes on crime films, including The Honeymoon Killers and The Harder They Come. Witness one-of-a-kind horror in Bill Gunn's landmark vampire film Ganja and Hess and Nobuhiko Obayashi's infamous and indescribable Hausu. Absorb the boundary-pushing documentary-style trilogy The Decline of Western Civilization, which throws you into indelible moments in the punk and metal music scenes. And marvel at pure '80s oddities like Mac and Me and The Garbage Pail Kids. From Possession to Polyester and Beyond the Valley of the Dolls to Xanadu, no two films are alike in this compendium. Just sit back and prepare to be surprised, amused, and entertained by this celebration of the stars, filmmakers, and stories behind fifty of the most beguiling and unforgettable movies ever to hit the screen--